Use of rituximab in the treatment of pemphigus vulgaris in a juvenile patient - Cisoń, Hanna Róża; Baran, Wojciech; Białynicki-Birula, Rafał (Dermatology Review/Przegląd Dermatologiczny, 2023)
Introduction: Pemphigus vulgaris is a chronic autoimmune blistering disorder characterised by the production of autoantibodies against desmogleins, resulting in intraepithelial blister formation. Despite advancements in treatment options, some patients experience disease progression and an inadequate response to conventional therapies. Rituximab, a monoclonal chimeric antibody targeting CD20 on B-cells, has shown promise as an alternative therapeutic option. Case report: In this case report, we present the management of a 14-year-old child with pemphigus vulgaris who exhibited disease progression despite conventional treatment modalities. The patient was administered rituximab therapy, resulting in significant clinical improvement and disease control. Conclusions: The utilisation of rituximab as an adjunct or alternative therapy in refractory pemphigus cases offers a valuable treatment option. Further studies and long-term follow-up are necessary to determine the optimal dosing regimen and evaluate the safety and efficacy of rituximab in paediatric pemphigus patients.